PENGARUH DISIPLIN KERJA DAN FASILITAS KESEHATAN TERHADAP MUTU PELAYANAN PUSKESMAS DI KOTA BATURAJA - Ineta Satmawati; Rini Efrianti; Fifian Permata Sari (Media Bina Ilmiah, 2025)
The quality of health services is a measure of health services, both individual and community (population) in order to increase the scope of expected health outcomes such as increasing health levels and decreasing morbidity or pain levels, as well as being dynamic and consistent with the development of health professional knowledge. Based on the results of the study and discussion, it can be concluded that: Work discipline and work facilities simultaneously have a significant effect on the quality of services at the Baturaja City Health Center, OKU Regency with a determination coefficient (r2) of 0.920. This means that 92.0% of the high and low quality of health services at the Baturaja City Health Center, OKU Regency is influenced by work discipline and work facilities, the remaining 18.0% is determined by other factors not observed in this study